Exploiting functional regions in the viral RNA genome as druggable entities - Dehua Luo; Yingge Zheng; Zhiyuan Huang; Zi Wen; Lijun Guo; Yingxiang Deng; Qingling Li; Yuqing Bai; Shozeb Haider; Dengguo Wei (eLife)
RNA-targeting compounds or small interfering RNAs (siRNAs) offer a potent means to control viral infections. An essential prerequisite for their design depends on identifying conserved and functional viral RNA structures in cells. Techniques that probe RNA structures in situ have recently been developed including SHAPE-MaP, which has been helpful in the analysis of secondary structures of RNA. In this study, we report on the application of SHAPE-MaP to the porcine epidemic diarrhea virus RNA genome to categorize different functional regions, including potential quadruplex-forming sequence and target sites of siRNA. Our results show that these structures can be exploited to inhibit viral proliferation and that SHAPE-MaP is an effective method to identify secondary structures in RNA genomes.